Eponymy as an integral part in English terminology of oil and gas transportation and storage - I. A. Shuytseva (Омский научный вестник: Серия "Общество. История. Современность")
The paper describes the research results of English terminological combinations containing eponyms in the sublanguage of oil and gas transportation and storage. The explanation is given of how terms-eponyms enter into industry-specific terminology. The view points of Russian and foreign terminologists on eponyms in a scientific and technical terminology and the functions which eponyms perform are presented. Models of formation for eponymic terminological combinations are analyzed, their structure and composition are examined. The phenomena of abbreviation and polysemy in the described terminology are defined